Membangun Ketahanan Pangan Ternak Unggas melalui Budidaya Larva Maggot di Desa Binong Pamarayan Kabupaten Serang - Ade Manggala Hardianto; Muhammad Angga Anggriawan (Penerbit Goodwood, 2023)
Purpose: The increase in population has an impact on the increase in waste and becomes environmental pollution. Waste management often offered, so we initiated the productivity of waste management in a wise way, including cultivating the Black Soldier Fly (BSF) maggot fly. Food security for livestock has become an important issue because food prices continue to skyrocket. Binong Village, Serang Regency, is a village assisted by Bina Bangsa University in processing organic waste for the cultivation of BSF maggot flies. Its advantages include being an alternative solution for processing vegetable/fruit waste naturally (does not contain chemicals) and reducing the burden of animal feed. Methodology: The research method is through an active participation approach (Participatory Action Research), namely the involvement of researchers with local communities in order to develop groups of potential breeders. Results: The results of BSF fly maggot cultivation have contributed to reducing the cost of animal feed production, and reducing food waste (vegetables/fruits) so that they can be developed into national livestock food security.